The Book of Dust: La Belle Sauvage - Pullman, Philip 1946- (New York Alfred A. Knopf, 2017)
When Malcolm finds a secret message inquiring about a dangerous substance called Dust, he finds himself embroiled in a tale of intrigue featuring enforcement agents from the Magisterium, a woman with an evil monkey daemon, and a baby named Lyra.
Accelerated Reader AR
Keywords: Adventure stories -- Young adult fiction; Spy stories -- Young adult fiction; Belacqua, Lyra (Fictitious character) -- Young adult fiction; Friendship -- Young adult fiction; Familiars (Spirits) -- Young adult fiction; Taverns (Inns) -- Young adult fiction; Infants -- Young adult fiction; Magic -- Young adult fiction